SU‐E‐J‐182: Patient Specific Assessment of External Radiation Exposure to Bystanders Interacting with Patients Following 131I Therapy - Han, E (Med Phys, 2012)
Purpose: Conventional calculation methods of patient release criteria for compliance with NRC regulations are based on the assumption that both patient and bystander are each a single point in space. This study was intended to assess the patient‐specific external radiation exposure to a bystander interacting with the patient following radionuclide therapy with 131I. Methods: 131I‐sodium iodide treatment for hyperthyroidism and thyroid cancer and 131I‐tositumomab treatment of non‐Hodgkin's lymphoma were considered. 131I distribution provided by the patient SPECT image was rendered on the SPECT‐fused CT images. The CT images were then imported to a Monte Carlo based simulation code, MCNPX 2.7, as a source phantom. For a target phantom, we employed the adult male hybrid phantom developed at the University of Florida and National Cancer Institute. A single orientation ‐ patient and a bystander facing one another at 1.0 m ‐ was considered. S factors (dose per unit cumulative activity (A)) for each organ in a bystander was obtained from the MC calculations and effective dose (EDE) per A was calculated based on tissue‐weighted individual organ doses. The results were compared with the calculations using UF/NCI adult hybrid source/target phantoms and the revised adult ORNL stylized source/target phantoms. Results: EDE per A of the stylized phantom was 1.5% higher than that of the hybrid phantom for uniform source localization in the thyroid. However, EDE per A of the hybrid phantom was 20% less than that of stylized phantoms for a torso source. The difference is attributed to the realistic shape of the frontal body comparing to the simple ellipsoidal trunk of the stylized phantom. Conclusions: Based on the realistic hybrid phantoms and accurate MC radiation transport calculation tools, patient specific dosimetry for a bystander is feasible. S factors will be calculated using the patient CT image with 131I bio‐distributions and hybrid phantoms.